A Case Report of Elderly Woman with Supraventricular Tachycardia associated with Intracranial Bleeding - Pranata, Raymond; Chintya, Veresa; Yonas, Emir; Damay, Vito (The Indonesian Heart Association, 2017)
Background The neurogenic cardiac injury is related to brain injury-induced catecholamine and neuro-inflammatory responses and is more likely in those with the most severe neurological insult. Case Report A 78 years-old female presented to the emergency department after being found lying on the floor with a laceration on the head. On physical examination GCS 3, BP 140/90 mmHg, HR 190 bpm, respiratory rate 25x/minute. PMH of hypertension and diabetes were denied. ECG showed supraventricular tachycardia of 186 bpm. Laboratory exams showed hyponatremia, hypokalemia, and leukocytosis. CT scan revealed subarachnoid hemorrhage, intracerebral hematomas, chronic subdural hematoma, midline shift and subfalcine herniation. The systemic catecholamine ‘storm’ driven by the central neuroendocrine axis massively increases sympathetic outflow, activates the adrenal gland and may lead to arrhythmia. Increased ICP, Midline shift, and subsequent physical compression of the brainstem and hypothalamic autonomic centers can trigger catecholamine responses that could instigate an arrhythmia. Suboptimal cardiac output and cerebral perfusion worsen secondary brain injury leading to a worse prognosis. Since cardioversion failed, amiodarone was administered. Cardioversions failed to convert to sinus rhythm and amiodarone was administered. Therapy to reduce intracranial pressure was also administered. The patient passed away 4 hours after admission. Conclusion Arrhythmia related to brain injury may lead to suboptimal cerebral perfusion and leads to further autonomic derangements leading to a vicious cycle of cerebral and cardiovascular injuries. This condition should be accounted for swiftly to prevent secondary brain injuries and myocardial ischemia.   Abstrak Latar Belakang Respons katekolamin dan radang terhadap cedera otak menyebabkan cedera jantung neurogenik yang lebih sering terjadi pada kerusakan neurologis yang berat. Laporan Kasus Seorang perempuan 78 tahun datang ke IGD setelah ditemukan tergeletak di lantai dengan robek pada kulit kepala. Pada pemeriksaan fisik ditemukan GCS 3, TD 140/90 mmHg, detak jantung 190 kali/menit, laju pernafasan 25 kali/menit. Riwayat hipertensi dan diabetes disangkal. EKG menunjukan takikardia supraventrikular takikardi 186 kali/menit. Pemeriksaan laboratorium menunjukan hiponatremia, hipokalemia dan leukositosis. CT scan menunjukan perdarahan subaraknoid, perdarahan intraserebral, perdarahan subdural kronis, midline shift dan herniasi subfalcine. Badai katekolamin sistemik yang dicetuskan oleh aksis neuroendokrin pusat meningkatkan outflow simpatetik yang mengaktifkan kelenjar adrenal dan menyebabkan aritmia. Peningkatan tekanan intrakranial, midline shift, dan penekanan batang otak serta pusat autonomik hipotalamus dapat mencetuskan respon katekolamin yang dapat menyebabkan aritmia. Curah jantung yang tidak optimal dan perfusi otak yang buruk menyebabkan cedera otak sekunder yang mengarah pada prognosis yang buruk. Karena kardioversi gagal merubah irama menjadi sinus maka amiodaron diberikan. Pengobatan untuk menurunkan tekanan intrakranial juga diberikan. Pasien meninggal 4 jam setelah masuk rumah sakit. Kesimpulan Aritmia yang berhubungan dengan cedera otak dapat menyebabkan perfusi otak yang suboptimal serta menyebabkan ketidakteraturan otonom dan menyebabkan lingkaran setan kerusakan otak dan jantung-pembuluh darah. Hal ini harus segera ditangani untuk mencegah cedera otak sekunder dan iskemi miokardial.